Effects of Tsumura Chorei-to and Tsumura Chorei-to-go-shimotsu-to on patients with urethral syndrome - Sugaya, K (Hinyokika kiyo. Acta urologica Japonica, 1992)
Tsumura Chorei-to or Tsumura Chorei-to-go-shimotsu-to, was administered to 71 female patients with urethral syndrome 2.5 g three times a day for four weeks. Total efficacy rate of Tsumura Chorei-to in 34 cases was 71%. Tsumura Chorei-to was effective against pollakisuria, miction pain or discomfort, sense of residual urine and lower abdominal discomfort. Total efficacy rate of Tsumura Chorei-to-go-shimotsu-to in 37 cases was 57%. Tsumura Chorei-to-go-shimotsu-to was effective against dysuria, sense of residual urine and lower abdominal discomfort. Uutoward effect rates of Tsumura Chorei-to and Tsumura Chorei-to-go-shimotsu-to were 6% and 14%, respectively. Many of the untoward effects of these two drugs were epigastral discomfort. These two drugs are thought to be effective on patients with urethral syndrome